Ketosis suppression and ageing (KetoSAge): the effect of suppressing ketosis on SHBG and sex hormone profiles in healthy premenopausal women, and its implications for cancer risk and therapy - Cooper, Isabella D.; Petagine, Lucy; Soto-Mota, Adrian; Duraj, Tomás; Seyfried, Thomas N.; Lee, Derek C.; Cooper, Naja; Kyriakidou, Yvoni (Frontiers in Nutrition, 2026)
IntroductionInsulin resistance and hyperinsulinaemia significantly influence female hormone regulation and reproductive health. Despite increasing research, the complex pathways by which nutritional and metabolic signals regulate reproductive function remain poorly understood. Sex hormone-binding globulin (SHBG) is a key protein whose function is modulated by hyperinsulinaemia, liver function, and metabolic status, thereby influencing the active signalling of circulating sex steroids and intracellular signalling, which in turn, impacts endocrine and reproductive physiology. Consequently, SHBG serves as a valuable biomarker for understanding the metabolic-hormonal interactions within the endocrine axis. Ketogenic diets have demonstrated efficacy in reversing insulin resistance, resolving markers of liver disease, and improving metabolic health. In this study, we investigated the impact of suppressing ketosis (hypoketonaemia) on biomarkers of female reproductive and endocrine function in the Ketosis Suppression and Ageing cohort.MethodsTen lean (BMI, 20.52 kg/m2 ± 1.39), healthy, premenopausal women (mean age, 32.30 ± 8.97 years), who maintained nutritional ketosis for an average of 3.9 years (± 2.3), participated in a three-phase intervention trial: 21-days of baseline data-collection in euketonaemia, 21-days of hypoketonaemia, and 21-days return to euketonaemia.ResultsSuppression of ketosis resulted in a significant 0.67-fold decrease in SHBG levels (p = 0.0015). SHBG was significantly and inversely associated with insulin (p = 0.0010), insulin resistance score (HOMA-IR; p = 0.0012), glucose ketone index (GKI; p = 0.0183), leptin (p = 0.0016), insulin-like growth factor-1 (IGF-1; p = 0.0172), free T3 (p = 0.0001), and gamma-glutamyl transferase (GGT; p = 0.0024). A significant positive association between SHBG and GLP-1 (p = 0.0295) was observed. Menstrual cycle phase was a statistically significant predictor of follicle-stimulating hormone (FSH) levels, with higher FSH levels during ovulation than during the follicular phase (p = 0.0097).DiscussionSHBG is a sensitive biomarker of metabolic-endocrine status, with broader implications for cancer, and reproductive function. Chronic hypoketonaemia negatively affects SHBG production and hormonal balance. The implications of sex-hormone regulation for cancer prevention and therapy are discussed.